Introducing Different Levels of Reuse to a Hypermedia Authoring Language with Macros and Templates - Terças, Lucas de Macedo; Moraes, Daniel de Sousa; Lima, Thacyla de Sousa; M. Neto, Manoel Carvalho; Soares Neto, Carlos de Salles (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
Reuse techniques are a common way of decreasing the development cost and time whilst increasing the quality of applications. The sNCL language was first designed intending to decrease the verbosity required by hypermedia applications for the Ginga-NCL middleware, at the same time keeping equal expressiveness power. However, it removed almost all the reuse elements of NCL. This work presents the reuse elements introduced on the language as a method of increasing the reuse for Digital TV applications developers. It consists of macro elements, that can be used to reuse any generic information and a template system, a common theme in the literature as a form of increasing or introducing reuse on hypermedia authoring. The paper shows an study case with positive results of the new features when specifying five Digital TV applications from a public repository.